A synergistic combination of reduced graphene oxide and antimony nanoparticles for estriol hormone detection - Cesarino, Ivana [UNESP]; Cincotto, Fernando H.; Machado, Sergio A. S. (Elsevier B.V., 2015)
In this study, the modification of reduced graphene oxide (rGO) with antimony nanoparticles (SbNPs) for determination of estriol in natural water is presented for the first time. The morphology and the electrochemical performance of the rGOSbNPs composite were characterised by scanning electron microscopy and cyclic voltammetry, respectively. The synergistic combination of rGO sheets and Sb nanoparticles yielded a limit of detection (LOD) of 0.5 nmol L-1 (0.14 mu g L-1) for estriol hormone, the lowest LOD for estriol reported in the literature to our knowledge. The proposed device was successfully applied in the determination of estriol in a natural water sample, and is a promising platform for a simple, rapid, direct and ultrasensitive analysis of estriol.
Keywords: Antimony nanoparticle; Graphene; Composite material; Estriol hormone